The influence of work professionalism and quality of public services on employee performance at the Bappelitbangda Office of Teluk Bintuni Regency, West Papua Province - Ansyar Ansyar; Muhammad Guzali Tafalas; Selmi Dedi (Universitas Muhammadiyah Enrekang, 2025)
The provision of good quality public services is still considered lacking to the community, especially for people in Teluk Bintuni Regency. This is due to discriminatory treatment in providing services to the community, low seriousness in providing services, especially in the consistency of working hours and lack of response to community complaints. To overcome these conditions, it is necessary to make efforts to improve the quality of public service delivery on an ongoing basis. The provision of quality services to the public is very intersecting with the bureaucracy. One of the bureaucracies in Teluk Bintuni Regency is the Bappelitbangda Office or commonly called Bapedda. The improvement in the quality of public services is suspected to increase if service providers carry out work professionalism. This has a partial effect. It has also been tested that there is a partial positive influence between professionalism on the quality of employee performance at the Bappelitbangda office of Teluk Bintuni Regency, West Papua..